2018
DOI: 10.1007/s00344-018-9792-0
|View full text |Cite
|
Sign up to set email alerts
|

24-Epibrassinolide as a Modifier of Antioxidant Activities and Membrane Properties of Wheat Cells in Zearalenone Stress Conditions

Abstract: The mechanism of action of brassinosteroids (BRs) in plant cells under stress has not been fully explained, despite ample evidence of their protective effects. The aim of this study was to investigate the significance of physicochemical properties of cell membranes during an interaction with BRs under stress conditions induced by a mycotoxin zearalenone (ZEA). Experiments were performed in in vitro cultures of wheat cells obtained from immature embryos of tolerant and sensitive genotypes. ZEA added to media (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…BR decreases vascular wilt severity because it can participate in several physiological processes that activate the defense system (Anwar et al, 2018;Peres et al, 2019). This synthetic elicitor can also be involved in the expression of pathogenesisrelated proteins, which lead to an increase in the resistance to pathogens (Ding et al, 2009b;Filek et al, 2018;Saini et al, 2015). In addition, SA can contribute to the regulation of defense against biotrophic and hemibiotrophic pathogens; it plays a key role in the systemic acquired resistance of plants, the modulation of the hypersensitivity response associated with programmed cell death, the increase in the levels of reactive oxygen species, and the activation of lipid peroxidation (Bernsdorff et al, 2016; Dempsey and Klessig, 2017; Qi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…BR decreases vascular wilt severity because it can participate in several physiological processes that activate the defense system (Anwar et al, 2018;Peres et al, 2019). This synthetic elicitor can also be involved in the expression of pathogenesisrelated proteins, which lead to an increase in the resistance to pathogens (Ding et al, 2009b;Filek et al, 2018;Saini et al, 2015). In addition, SA can contribute to the regulation of defense against biotrophic and hemibiotrophic pathogens; it plays a key role in the systemic acquired resistance of plants, the modulation of the hypersensitivity response associated with programmed cell death, the increase in the levels of reactive oxygen species, and the activation of lipid peroxidation (Bernsdorff et al, 2016; Dempsey and Klessig, 2017; Qi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The ZEA presence in cells, at hormonal concentrations, stimulates the flowering induction of plants (Biesaga-Kościleniak and Filek 2010). However, at higher than hormonal amounts, it may stimulate oxidative stress and generation of oxygen radicals, which result in destruction of biologically important molecules, such as proteins, lipids, and DNA (Filek et al 2017(Filek et al , 2018. Thus, searching for substances that reduce this toxin accumulation and diminish the biochemical consequences of its action is of special importance.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of mycotoxin accumulation in the tissues 12 , cells 13 and cellular organelles 14,15 of plants that constitute the basics of human diet has prompted the search for methods that prevent the absorption of these substances. Mycotoxins consumed with food accumulate in animal and human cells 16,17 , act as carcinogens and initiate pathogenic changes in various organs 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…The different methods are used for detoxification of mycotoxins including the biological neutralization by microorganisms, mainly bacteria 2428 , and saccharomyces 29 as well as by physical 30,31 and chemical 32 adsorbents. In our previous works, it was demonstrated the reduced ZEN uptake resulting from both foliar administration and seed soaking in brassinosteroids (24-EBR) – phytohormones naturally occurring in cells, as well as from treatment with selenium ions, the accumulation of which is beneficial under oxidative stress conditions 14,15,33 . We suggested that brassinosteroids, with their hydrophilic-hydrophobic molecular structure similar to ZEN, may bind to the lipid part of the bilayer and displace ZEN from membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation